STRANGE AT TRACTOR DIMENSION OF SURFACE RADIO REFRACTIVITY OVER INDIAN STATIONS (MAUSAM, 1994)
1 , ~1 1 1t: th e Ih 1.....I)· of tldr-n n i ni... ric ...h no s, th e r.h til l n: fml,'llvit)" hil s been \ llh ti l'\ t for l'i ~1 1 1r.' I'l l".'l\lali\'l" suuions in 1IIlI ia a n J l1iKU:-" 1.'11i n relat ion to st rn age ut truc to r dimcnsto n. It .....;,.. found th a t SL'( to n iner .Hl.IIlWlt"l", nrc nee..h·,1 10 p redict r.tJiu refracti vity OWl the Ind ian region similar lu tluu re pone..t Iur other" l l1 l ll ~ I'I l\' n ;; phe n. uuvuu ALso. inl a n d an d .;tH!